2013
DOI: 10.5560/znb.2013-3150
|View full text |Cite
|
Sign up to set email alerts
|

BIOnic Liquids: Imidazolium-based Ionic Liquids with Antimicrobial Activity

Abstract: We have synthesized twelve new ionic liquids composed of an imidazolium-based cation in combination with an anion that shows antiobiotic or analgesic activity. These "BIOnic Liquids" have been tested towards their antibiotic activity in a standardized microbiological assay. A surprizingly large number of compounds shows high activity towards a set of bacteria which cannot be explained as simple cumulative effects. The general concept opens up completely new possibilities for the future development of pharmaceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…In a previous work, we investigated the influence of imidazolium cations on the activity of AMPs [ 72 , 73 ]. Based on observations that imidazolium cations, as part of so-called ionic liquids [ 73 , 129 ], exhibit antimicrobial activity, these compounds were covalently and non-covalently added to AMPs.…”
Section: Modified Amps and Amp Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous work, we investigated the influence of imidazolium cations on the activity of AMPs [ 72 , 73 ]. Based on observations that imidazolium cations, as part of so-called ionic liquids [ 73 , 129 ], exhibit antimicrobial activity, these compounds were covalently and non-covalently added to AMPs.…”
Section: Modified Amps and Amp Conjugatesmentioning
confidence: 99%
“…In a previous work, we investigated the influence of imidazolium cations on the activity of AMPs [ 72 , 73 ]. Based on observations that imidazolium cations, as part of so-called ionic liquids [ 73 , 129 ], exhibit antimicrobial activity, these compounds were covalently and non-covalently added to AMPs. AMPs used for coupling were sC18 [ 125 ] and the LL-37 peptide, which also belongs to the group of cathelicidins and is a two-amino acid truncated form of FALL-39 [ 13 , 130 ].…”
Section: Modified Amps and Amp Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15–17 ] By contrast, the imidazolium‐containing ionic liquid (IL) ligands which essentially consist of an aromatic heterocycle containing two nitrogen atoms, with one in the cationic form, are perhaps the most widely studied in the biological field because of their unique physical and chemical properties. [ 18–20 ] Moreover, extensive biochemical and pharmacological studies have confirmed imidazole as effective compounds in treating various strains of microorganisms. [ 21–23 ] Their antibacterial and antifungal effects are attributed to cationic interactions with negatively charged parts of bacterial membranes.…”
Section: Introductionmentioning
confidence: 99%
“…With these special properties, ILs have been widely used in many applications, such as batteries, 24,25 catalysis, [26][27][28] drug delivery 29,30 and solvents [31][32][33] . A recent patent described a FO process to use ILs as draw solutions, but didn't mention the regeneration methods.…”
Section: Introductionmentioning
confidence: 99%